Chemical approaches targeting the hurdles of hepatocyte transplantation: mechanisms, applications, and advances - Shi, Huanxiao; Ding, Yi; Sun, Pingxin; Lv, Zhuman; Wang, Chunyan; Ma, Haoxin; Lu, Junyu; Yu, Bing; Li, Wenlin; Wang, Chao (Frontiers in Cell and Developmental Biology, 2024)
Hepatocyte transplantation (HTx) has been a novel cell-based therapy for severe liver diseases, as the donor livers for orthotopic liver transplantation are of great shortage. However, HTx has been confronted with two main hurdles: limited high-quality hepatocyte sources and low cell engraftment and repopulation rate. To cope with, researchers have investigated on various strategies, including small molecule drugs with unique advantages. Small molecules are promising chemical tools to modulate cell fate and function for generating high quality hepatocyte sources. In addition, endothelial barrier, immune responses, and low proliferative efficiency of donor hepatocytes mainly contributes to low cell engraftment and repopulation rate. Interfering these biological processes with small molecules is beneficial for improving cell engraftment and repopulation. In this review, we will discuss the applications and advances of small molecules in modulating cell differentiation and reprogramming for hepatocyte resources and in improving cell engraftment and repopulation as well as its underlying mechanisms.